The Greek Revolution Through the Foreign Press. The Case of Newspaper the London Times in the Period 1821-1828 - Antoniades, Euripides (My University, 2023)
In 1821, the Greek Revolution movement, under the political influence that arose from the French revolution, and the corresponding movements in Italy, Germany and America, demanded the liberation of the nation and the establishment of an independent national state. Published topics in the British press regarding the Greek Revolution, focused on: a)the right of the Greeks to claim their freedom from Turkish domination in order to establish an independent state based on the principle of national autonomy, b)criticism regarding Turkish rule as illegal and the power of the Ottoman Sultan as arbitrary, c)the recognition of the Greek identity and its distinction from the Turkish one and d)the endorsement Greeks as the descendants of ancient Greeks. The London Times is a print publication that presents, in chronological or thematic order, the news, opinions or announcements about the most important events that have occurred in a place during a specified period of time. A combination of qualitative and quantitative content analysis was applied. An attempt was made to record Greek Revolution references along with the usage of specific words and expressions that contribute to the representation of the historical events and their exposure to the reading public. Key finds of this research reveal that a)there was a frequency of passionate daily articles concerning the events in Greece, their length, and context in The Times of London, b)he British public opinion was influenced by this particular newspaper and c) he newspaper published various news about the revolution by adopting the role of animator of the Greek struggle. In fact, this type of news was the main substance of the The London Times’ structure, establishing a positive image about the Greek Revolution contributing to the European diplomatic development. These factors offered a change in the attitude of the British and Russians respectively assuming a positive approach towards Greece.
Keywords: Greece; Revolution; Press; The London Times; Great Britain; Mass Media